Asteropsins B–D, sponge-derived knottins with potential utility as a novel scaffold for oral peptide drugs - Li, Huayue; Bowling, John J.; Su, Mingzhi; Hong, Jongki; Lee, Bong-Jin; Hamann, Mark T.; Jung, Jee H. (Biochimica et biophysica acta, 2014)
Known linear knottins are unsuitable as scaffolds for oral peptide drug due to their gastrointestinal instability. Herein, a new subclass of knottin peptides from Porifera is structurally described and characterized regarding their potential for oral peptide drug development. Asteropsins B–D (ASPB, ASPC, and ASPD) were isolated from the marine sponge Asteropus sp. The tertiary structures of ASPB and ASPC were determined by solution NMR spectroscopy and that of ASPD by homology modeling. The isolated asteropsins B–D, together with the previously reported asteropsin A (ASPA), compose a new subclass of knottins that share a highly conserved structural framework and remarkable stability against the enzymes in gastrointestinal tract (chymotrypsin, elastase, pepsin, and trypsin) and human plasma. Asteropsins can be considered as promising peptide scaffolds for oral bioavailability. The structural details of asteropsins provide essential information for the engineering of orally bioavailable peptides. •An unusual subclass of knottin peptides from a sponge•Peptides share highly conserved structural framework.•Solution NMR structures were analyzed in detail.•Showed remarkable stability against key gastrointestinal enzymes•Potential scaffold for oral peptide drugs